2019
DOI: 10.1039/c8ra10303h
|View full text |Cite
|
Sign up to set email alerts
|

Do soft anions promote protein denaturation through binding interactions? A case study using ribonuclease A

Abstract: Soft anions promote protein folding through binding backbone CH and CH2 groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 81 publications
2
31
0
Order By: Relevance
“…Accordingly, to investigate whether the AmpC mutations affect enzyme stability, the melting temperatures (Tm) of the WT and mutant AmpC enzymes were measured. The Tm determined for WT AmpC (i.e., PDC-1 from P. aeruginosa PAO1) (55.33˚C) is comparable to those of other WT AmpC analogues, including E. coli AmpC (54.6˚C) (Beadle et al 1999) (Francisco et al 2019), where ∆Hunfolding is the unfolding enthalpy, which is positive during thermal denaturation (Pica and Graziamo 2016), and Tm is the melting temperature of the WT AmpC enzyme. That is to say, these mutations decrease the stability of AmpC which in turn increases its flexibility and dynamics at room temperature.…”
Section: Relationship Between Ampc Stability Flexibility and Activitymentioning
confidence: 67%
“…Accordingly, to investigate whether the AmpC mutations affect enzyme stability, the melting temperatures (Tm) of the WT and mutant AmpC enzymes were measured. The Tm determined for WT AmpC (i.e., PDC-1 from P. aeruginosa PAO1) (55.33˚C) is comparable to those of other WT AmpC analogues, including E. coli AmpC (54.6˚C) (Beadle et al 1999) (Francisco et al 2019), where ∆Hunfolding is the unfolding enthalpy, which is positive during thermal denaturation (Pica and Graziamo 2016), and Tm is the melting temperature of the WT AmpC enzyme. That is to say, these mutations decrease the stability of AmpC which in turn increases its flexibility and dynamics at room temperature.…”
Section: Relationship Between Ampc Stability Flexibility and Activitymentioning
confidence: 67%
“…The aqueous solubility of hydrophobic molecules is particularly sensitive to salt addition and this property has found use in diverse chemical processes such as aqueous phase organic chemistry, salting‐out extraction, hydrophobic interaction chromatography and the synthesis of colloids and membrane vesicles . The presence of salt also affects the thermodynamic properties of biological macromolecules and it has been demonstrated that ion‐specific changes in the solubility of hydrophobic protein moieties is a major contributor to salt induced perturbations to the overall protein folding free energy . This being said, we still lack a complete mechanistic picture of how the presence of ions modulates the solubility of hydrophobic molecules.…”
Section: Introductionmentioning
confidence: 99%
“…ref. 18 ). A fact overlooked in later expositions of this theory is the linear dependence of the specific heat Δ c p on salt concentration.…”
Section: Introductionmentioning
confidence: 99%